Stimulasi Perkembangan Aspek Seni Anak Usia Dini - Henny, Henny; Saleh, Rachman; Marwah, Marwah; Kurniati, Asma; Suhardin, Neka (UIR PRESS, 2023)
This study aims to determine the process of stimulating early childhood artistic development in Banca Patola Kindergarten, Baubau City. This research is a qualitative descriptive study. Data is collected by observing, interviewing, and documenting. Data were analyzed by reducing, displaying and verifying. The results showed that the process of stimulating children's artistic development was carried out with activities such as: (1) humming or singing while doing something; (2) be creative with beads, origami paper and natural materials; (3) sanitary activities such as mixing colors, finger painting; (4) drawing in various ways and forms; (5) coloring activities. In addition, several stimulations that can be applied to increase the achievement of artistic development aspects in Banca Patola Kindergarten, namely: (1) the teacher's role is to provide support and facilities for children to listen to the songs they like; (2) the teacher always gives appreciation in the form of praise; (3) the teacher facilitates activities that stimulate children's art; (4) the teacher gives rewards to children for their achievements in activities.